Antioxidant activity of isoespintanol and thymol in cryopreserved stallion semen - Restrepo B., Giovanni (2018)
Isoespintanol from the leaves of Oxandra cf xylopioides and thymol present in the essential oils of thyme (Thymus vulgaris L) and oregano (Origanum vulgare L) is known for their activity as antioxidants in different media. In this study, the antioxidant activity of isoespintanol and thymol in cryopreserved stallion semen was evaluated. The semen of five Colombian Creole horses was collected and subjected to a freezing protocol, in an extender supplemented with isoespintanol or thymol. The production of reactive oxygen species and the lipid peroxidation of the thawed semen were evaluated. As a result, a post-thawing reduction of the production of reactive oxygen species of semen was observed due to the effect of both antioxidants, whereas no difference was found in the lipid peroxidation levels of post-thawed semen. Isoespintanol and thymol act as antioxidants in stallion semen subjected to cryopreservation.